Anteseden Tata Kelola Wakaf di Indonesia - Agha Karnys Izza Muhammad; Fadel Fadhillah; Muhammad Jihad (Veteran Economics, Management, & Accounting Review, 2025)
This study aims to analyze the implementation of waqf governance in Indonesia using a descriptive qualitative approach, based on data from the National Waqf Index (NWI) for the years 2020 and 2021 in four provinces: DKI Jakarta, Bali, East Kalimantan, and Aceh. The results show that three provinces experienced significant increases in their NWI scores due to operational funding support from local governments, increased training frequency for nazhir, and improvements in certified nazhir ratios and waqf land management. In contrast, Aceh Province experienced a decline in its score due to the absence of submitted data in 2021. The study highlights the importance of consistent reporting, strengthening institutional capacity, and adopting digital innovations in waqf governance. Moreover, public understanding of contemporary waqf concepts remains low, necessitating public education and optimization of the role of the Indonesian Waqf Board (BWI). With these strategic steps, waqf has the potential to become an effective Islamic social finance instrument for national development. Keywords: Waqf, NWI, Governance, Institutional Capacity, Digitalization   Abstrak Penelitian ini bertujuan untuk menganalisis implementasi tata kelola wakaf di Indonesia melalui pendekatan deskriptif kualitatif, dengan menggunakan data National Waqf Index (NWI) tahun 2020 dan 2021 di empat provinsi: DKI Jakarta, Bali, Kalimantan Timur, dan Aceh. Hasil menunjukkan bahwa tiga provinsi mengalami peningkatan signifikan dalam skor NWI akibat dukungan dana operasional dari pemerintah daerah, peningkatan frekuensi pelatihan nadzir, serta perbaikan rasio nazir bersertifikasi dan pengelolaan tanah wakaf. Sebaliknya, Provinsi Aceh mengalami penurunan skor karena tidak menyampaikan data pada tahun 2021. Penelitian ini menyoroti pentingnya konsistensi pelaporan, penguatan kapasitas kelembagaan, serta inovasi digital dalam tata kelola wakaf. Selain itu, pemahaman masyarakat terhadap konsep wakaf kontemporer masih rendah, sehingga diperlukan edukasi publik dan optimalisasi peran Badan Wakaf Indonesia (BWI). Dengan langkah strategis tersebut, wakaf berpotensi menjadi instrumen keuangan sosial Islam yang efektif untuk pembangunan nasional. Kata kunci: Wakaf, NWI, Tata Kelola, Kelembagaan, Digitalisasi.